Effects of hydration state and resistance exercise on markers of muscle damage - Yamamoto, L. M.; Judelson, D. A.; Farrell, M. J.; Lee, E. C.; Armstrong, L. E.; Casa, D. J.; Kraemer, W. J.; Volek, J. F.; Maresh, C. M. (The Journal of Strength and Conditioning Research, 2008)
It is well established that resistance exercise can damage muscle tissue, but the combined effects of hypohydration and resistance exercise on muscle damage are unclear. Two common circulating markers of muscle damage, myoglobin (Mb) and creatine kinase (CK) may be attenuated by fluid ingestion post-exercise. The purpose of this study was to examine the combined effect of resistance exercise and hydration state on muscle damage. Seven healthy resistance-trained males (age = 23 +/- 4 years; body mass = 87.8 +/- 6.8 kg; body fat = 11.5 +/- 5.2%) completed 3 identical resistance exercise bouts (6 sets of up to 10 repetitions of the back squat) in different hydration states: euhydrated (HY0), hypohydrated ~2.5% body mass (HY2.5), and hypohydrated ~5.0% body mass (HY5). Subjects achieved desired hydration states via controlled water deprivation, exercise-heat stress, and fluid intake. Both Mb and CK were measured during euhydrated rest (PRE). Mb was also measured immediately post-exercise, 1 hour (+1H) and 2 hours (+2H) post-exercise; CK was measured at 24 and 48 hours post-exercise. Body mass decreased 0.2 +/- 0.4%, 2.4 +/- 0.4%, and 4.8 +/- 0.4% during HY0, HY2.5, and HY5, respectively. Mb concentrations increased significantly (effect size >=1, p < 0.05) from PRE (2.6 +/- 1.1, 3.5 +/- 2.8, and 3.2 +/- 1.6 nmol[middle dot]L-1) to +1H (5.3 +/- 3.4, 6.8 +/- 3.2, and 7.6 +/- 2.8 nmol[middle dot]L-1), and +2H (5.5 +/- 3.8, 6.2 +/- 3.0, and 7.2 +/- 3.0 nmol[middle dot]L-1) for HY0, HY2.5, and HY5, respectively, but were not significantly different between trials. CK concentrations remained within the normal resting range at all time points. Thus, hypohydration did not enhance muscle damage following the resistance exercise challenge. Despite these results, athletes are encouraged to commence exercise in a euhydrated state to maximize endogenous hormonal, mechanical, and metabolic benefits.